Pengaruh Metode Pembelajaran Blended Learning Asinkronus Terhadap Pembelajaran Passing Bawah Permainan Bola Voli Siswa Kelas VIII MTs Negeri 4 Karawang - Muhammad Agam Sidik; Rizki Agus Pramana; Saepul Ma’mun (Jurnal Ilmiah Wahana Pendidikan, 2023)
Grade VIII students at Madrasah Tsanawiyah Negeri 4 Karawang, West Karawang District, Karawang Regency are still in the medium category in the asynchronous blended learning method for learning motivation in passing under the volleyball game during the Covid-19 pandemic. This study aims to determine the level of motivation in learning to pass under the volleyball game during the Covid-19 pandemic in the scope of class VIII students at MTs Negeri 4 Karawang, West Karawang District, Karawang Regency. Then this research is a quantitative descriptive or quantitative descriptive research. The method used is a survey with data collection techniques through questionnaire filling tests. The subjects in this study were students of class VIII MTs Negeri 4 Karawang with a total of 70 students. Data analysis techniques use descriptive analysis as outlined in the form of percentages. Based on the results of the study, it can be concluded that the survey on the effect of the asynchronous blended learning method on the learning motivation of passing under the volleyball game for class VIII MTs Negeri 4 Karawang during the Covid-19 pandemic was in the "very high" category 4.29% (3 students) , "high" by 21.43% (15 students), "moderate" by 38.57% (27 students), "low" by 28.57% (20 students), "very low" by 7.14% ( 5 students). Based on the average value, namely 66.00% in asynchronous blended learning on the motivation for learning passing under volleyball games, it is in the "moderate" category with an average (mean) score of 66.